Practical arduino robotics : A hands-on guide to bringing your robotics ideas to life using a arduino - Kaul, Lukas (London : Packt publishing Ltd, 2023)
Every robot needs a "brain," and the Arduino platform provides an incredibly accessible way to bring your Arduino robot to life. Anyone can easily learn to build and program their own robots with Arduino for hobby and commercial uses, making Arduino-based robots the popular choice for school projects, college courses, and the rapid prototyping of industrial applications. Includes index
Keywords: Technology